Ancient documents and their contexts : First North American Congress of Greek and Latin Epigraphy (2011) - Bodel, John P., 1957-; Dimitrova, Nora Mitkova, 1971- (Brill Studies in Greek and Roman Epigraphy, 2014)
Ancient Documents and their Contexts contains the proceedings of the First North American Congress of Greek and Latin Epigraphy (San Antonio, Texas, 4-5 January 2011). It gathers seventeen papers presented by scholars from North America, Europe, and Australia at the first formal meeting of classical epigraphists sponsored by the American Society of Greek and Latin Epigraphy. Ranging from technical discussions of epigraphic formulae and palaeography to broad consideration of inscriptions as social documents and visual records, the topics and approaches represented reflect the variety of ways that Greek and Latin inscriptions are studied in North America today. Contributors are: Bradley J. Bitner, Sarah Bolmarcich, Ilaria Bultrighini, Patricia A. Butz, Werner Eck, John Friend, Peter Keegan, Jinyu Liu, Kevin McMahon, John Nicols, Nadya Popov-Reynolds, Carolynn E. Roncaglia, Stephen V. Tracy, Dennis E. Trout, Georgia Tsouvala, Steven L. Tuck, and Arden Williams.